CrCl3·6H2OAs an Environmentally Friendly and Efficient Catalyst for One-Pot,Synthesis of 2-oxo-and 2-thio-1,2,3,4-Tetrahydropyrimidines Under Solvent-Free Conditions - Mohamadpour, Farzaneh (Makara Journal of Science, 2018)
A one-pot, simple, and eco-friendly synthesis of 2-oxo-and 2-thio-1,2,3,4-tetrahydropyrimidines using a Biginelli condensation between β-keto esters (methyl or ethyl acetoacetate), aromatic benzaldehydes, and urea or thiourea in the presence of CrCl3·6H2O as an environmentally friendly and mild catalyst under solvent-free conditions has been performed. Based on reaction of benzaldehyde (1.0 mmol), ethyl acetoacetate (1.0 mmol), and urea (1.5 mmol), as well as 15 mol% of CrCl3·6H2O catalyst, the 82% yield was reached within 30 minute reaction time. The advantages of this methodology are solvent-free conditions, ease of handling, one-pot nature, low-cost, environmental friendliness, simple purification of products, and short reaction time.